KONSELING BEHAVIORAL DENGAN TEKNIK SHAPING UNTUK MENINGKATKAN KEDISIPLINAN SAAT DARING KELAS XI MA ABADIYAH GABUS - Duwi Oktofya; Arista Kiswantoro; Sumarwiyah Sumarwiyah (Universitas Muria Kudus, 2022)
Behavior counseling is creating a new, better condition through the learning process so that negative behavior can be eliminated and changing adaptive behavior by strengthening expected behavior and eliminating unexpected behavior and trying to find new ways of behaving. The subjects students of MA Abadiyah Gabus year 2021/2022. Data collection methods used are interviews, observation, and in-depth documentation so that later accurate data will be obtained on the problems studied, namely the problem of improving students in doing school online assignments.Based on the results of the study, it can be concluded that the factors that cause undisciplined in doing online learning assignments are two factors, internal and external.After counseling with SDI and AMR shaping techniques were able to eliminate unfavorable behaviors such as being able to control oneself for the spirit of learning and reduce playing games and open applications that are not so important.